Perancangan Aplikasi E-Commerce Produk Kesehatan Herbal Pada PT. Yabes Inovasi Prima Jakarta Selatan Berbasis Web Menggunakan Metode Waterfall - Ludina, Soma; Erlin Hidayah, Rika; Nafia, Nur; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The growth of the digital industry has increased health products, especially herbal products. Desoil Healthy Box Shop takes advantage of this opportunity by offering herbal products online. Changes in consumer preferences to web platforms or mobile applications are due to ease of ordering and product variety. To compete in the herbal industry, operational efficiency is important. Web-based sales systems automate orders, payments, and shipping, reducing manual workload and increasing productivity. This system also enables better service to customers through easy product browsing and accurate information about availability. Competitive advantage is the main focus. Implementing a web-based sales system can differentiate Healthy Box Store from competitors by providing easy access and a better shopping experience. PT Yabes Innovation Prima has tried marketing via Instagram and Facebook, but the results have not been satisfactory. This research aims to design a web-based e- commerce application for herbal health products using the Waterfall method to expand the market and increase turnover.